2019
DOI: 10.1097/pts.0000000000000220
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Systemic Cobaltism After Wear or Corrosion of Chrome-Cobalt Hip Implants

Abstract: Systemic arthroprosthetic cobaltism is an increasingly recognized complication of wear or corrosion of chrome-cobalt hip implants, may involve a large number of organ systems, and may occur with relatively low B[Co]. There is an urgent need to better define the overall scope of the problem and to develop screening and management strategies.This is an open-access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives License 4.0 (CCBY-NC-ND), where it is permissibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
99
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 36 publications
4
99
0
Order By: Relevance
“…neurologic and cardiac symptoms) were only seen at higher Co levels (> 700 µg/l). Applying these observations on the published cases of 'arthroprosthetic cobaltism', reviewed by Gessner et al 15 , Cheung et al 240 and Zywiel et al 16 , there are some contradictions. Zywiel et al 16 concluded that neurological (72%), cardiovascular (55%) and endocrine (50%) effects are most commonly seen in this condition, of which the former two also occurred for Co levels much lower than 700 µg/l and in several cases even below 300 µg/l.…”
Section: Systemic Health Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…neurologic and cardiac symptoms) were only seen at higher Co levels (> 700 µg/l). Applying these observations on the published cases of 'arthroprosthetic cobaltism', reviewed by Gessner et al 15 , Cheung et al 240 and Zywiel et al 16 , there are some contradictions. Zywiel et al 16 concluded that neurological (72%), cardiovascular (55%) and endocrine (50%) effects are most commonly seen in this condition, of which the former two also occurred for Co levels much lower than 700 µg/l and in several cases even below 300 µg/l.…”
Section: Systemic Health Effectsmentioning
confidence: 87%
“…The toxic potential of cobalt and the related health risks have been investigated thoroughly in animal and human toxicity studies. Previous reviews often focused on either one specific exposure setting and the related Co intake routes, toxicity mechanisms and clinical consequences [6][7][8][9][10][11][12][13][14][15][16] , or the effect of Co on a specific physiological system in different Co exposure settings [17][18][19][20][21][22][23] . A recent extensive review of Paustenbach et al 2 covered the main cobalt sources, intake routes, kinetics, underlying toxicity mechanisms and a critical evaluation of previously reported adverse health effects.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, only cobalt is notably toxic. [1][2][3][4][5] Globally, about 40 million patients have replaced hip, shoulder, or knee with about half residing in the USA. [6,7] Most have at least one CoCr component.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Furthermore, individuals having received endoprotheses were shown to exhibit elevated blood and/or urine cobalt concentrations, commonly referred to as arthroprosthetic cobaltism. 1,[18][19][20] In June 2019, a routine doping control urine sample was tested for cobalt and returned an atypically high level of cobalt of 24.3 ng/ mL, which was neither in agreement with pilot study data on a small number of athletes 10 Cyanocobalamin was unequivocally identified in the doping control urine sample by HRMS ( Figure 1). The intact molecular ion was observed in full-MS measurements, and diagnostic product ions obtained by collision-induced dissociation were detected and matched previous publications.…”
mentioning
confidence: 65%
“…Exceptionally high levels were found in urine samples of miners and inhabitants of the immediate environment of cobalt mines and workers of hard metal factories . Furthermore, individuals having received endoprotheses were shown to exhibit elevated blood and/or urine cobalt concentrations, commonly referred to as arthroprosthetic cobaltism …”
mentioning
confidence: 99%